OPTIMIZATION OF PROCESS PARAMETERS ON TENSILE SHEAR LOAD OF FRICTION STIR SPOT WELDED ALUMINUM ALLOY (AA5052-H112) - Armansyah Armansyah; Ho Hwi Chie (Universitas Mercu Buana, 2018)
Optimization of the process was still the issue in manufacturing. Investigation on the process parameters that effects to the property of welded structure were necessary. In this study, the AA5052-H32 sheets of 2 mm thick were welded using friction stir spot welding (FSSW) and tested via tensile shear load test to investigate the influence of spindle speed, tool depth, and dwell time to the tensile shear load of the joints. The result shows that in every set of parameter combination, exhibit interesting influence to the tensile shear load. The effect of spindle speed of 1000 rpm shown the good property in average 18.33 KN especially at tool depth of 3.5 mm. Furthermore, the effect of tool depth brought significant effect to the tensile shear load especially at 3.5 mm for each set of spindle speed and dwell time. The set of dwell time to parameter combination had no significant effect to the tensile shear load. The good tensile shear load could be achieved in the range of 17.7-19.3 KN at 3.5 mm of plunge depth and 1000 rpm of spindle speed, where the best one was 19.3 KN at 7s of dwell time.